High neutrophil-to-lymphocyte ratio predicts early neurological deterioration in spontaneous intracerebral hemorrhage patients - Wafaa S. Mohamed (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2021)
Abstract Background Intracerebral hemorrhage (ICH) is caused by bleeding, primarily into parenchymal brain tissue, and accounts for 9 to 27% of all strokes worldwide. Higher neutrophils, lower lymphocytes, and higher neutrophil-to-lymphocytes ratio (NLR) values predict worse outcomes after spontaneous intracranial hemorrhage (sICH) and could aid in the risk stratification of patients. Methods Eighty patients with sICH within the first 24 h of stroke onset and admitted into the neurology intensive care unit of an Egyptian university hospital and were assessed by GCS for consciousness level and NIHSS for stroke severity assessment, complete blood count, and special attention to NLR. Patients were reevaluated by GCS and NIHSS on the 7th day of the stroke. Early neurological deterioration (END) was defined as four points or a greater increase in the NIHSS score or two points or a greater decrease in GCS or death. Results END was recorded in 21.25% of patients while non-END was recorded in 78.75%. END was highly significantly associated with a low grade of GCS, high grade of NIHSS, elevated absolute lymphocyte count (ALC), and elevated NLR. Lower GCS score, higher NIHSS score, larger hematoma volume, and higher NLR values were independent predictors for END. The best cutoff of NLR in END prediction was > 9.1. Conclusion NLR is a trustworthy early predictor of sICH outcome.